2021
DOI: 10.1371/journal.pone.0259324
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level intersectional stigma reduction intervention to increase HIV testing among men who have sex with men in Ghana: Protocol for a cluster randomized controlled trial

Abstract: Background Men with have sex with men (MSM) in Africa face high levels of stigma due to elevated HIV exposure (actual or perceived), same-sex practices, and gender non-conformity. These stigmas are documented barriers to HIV prevention and treatment. Most stigma-reduction interventions have focused on single-level targets (e.g., health care facility level [HCF]) and addressed one type of stigma (e.g., HIV), without engaging the multiple intersecting stigmas that MSM encounter. Determining the feasibility and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Eligible HCF staff ( N = 200) included both clinical and non‐clinical staff employed at a hospital in the parent study [37]. Purposive sampling recruited staff likely to interact with MSM clients by selecting 60% of the sample from key departments (Antiretroviral therapy (ART) clinic, outpatient department, pharmacy and security/reception/management) and 40% from other departments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligible HCF staff ( N = 200) included both clinical and non‐clinical staff employed at a hospital in the parent study [37]. Purposive sampling recruited staff likely to interact with MSM clients by selecting 60% of the sample from key departments (Antiretroviral therapy (ART) clinic, outpatient department, pharmacy and security/reception/management) and 40% from other departments.…”
Section: Methodsmentioning
confidence: 99%
“…Eligible HCF staff (N = 200) included both clinical and nonclinical staff employed at a hospital in the parent study [37].…”
Section: Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Government-sponsored research in Ghana, we also acknowledge the settler colonial history of taxonomizing humans (in Africa, Asia, the Americas, and elsewhere) into groups in order to render them and their sociocultural practices more interpretable and manageable to individuals viewing and administering them through a Western intellectual lens (38,39). Except when making references to speci c sexual identity groups, we use 'MSM' in this paper to refer to the men in the qualitative sample who were recruited in a larger HIV-prevention trial based solely on their self-reported potential HIV risk exposure category classi cation, not on their sexualities (40). We offer this clari cation here as an act of resistance to common practices that uncritically reduce men into behaviors as "MSM", a dehumanizing practice that is entrenched in HIV-prevention literature (41) and one which is admittedly observable in our previous publications (24,(42)(43)(44).…”
Section: Specifying Terminology and Positionalitymentioning
confidence: 99%
“…It is well established that stigma is a social determinant that negatively in uences health and other material and social aspects of daily life in the populations subjected to it (8)(9)(10)(11). In Ghana, the nearly ubiquitous presence of stigma and discrimination toward men with same-gender sexual experiences has the potential to limit the opportunities for these men to achieve and maintain equity in health, well-being, socio-emotional development, and economic progress (12,13).…”
Section: Introductionmentioning
confidence: 99%